2016
DOI: 10.1186/s12866-016-0842-0
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma ovipneumoniae induces sheep airway epithelial cell apoptosis through an ERK signalling-mediated mitochondria pathway

Abstract: Background Mycoplasma ovipneumoniae (M. ovipneumoniae) is a species of Mycoplasma bacteria that specifically infects sheep and goat, causing ovine infectious pleuropneumonia. However, the mechanism underlying the pathogen-host interaction between M. ovipneumoniae and airway epithelial cells is unknown.MethodsA primary air-liquid interface (ALI) epithelial culture model generated from the bronchial epithelial cells of Ningxia Tan sheep (ovis aries) was employed to explore the potential mechanism of M. ovipneumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 61 publications
(68 reference statements)
1
19
1
Order By: Relevance
“…This observation is of particular mentioning to importance due to the fact that an inhibitor of ERK1/2 signaling is incapable of reducing the activation of caspase-3, indicating that CPS-induced apoptosis can be independent of ERK1/2 signaling and can progress alternatively through the JNK and p38 pathways. Of note, this observation was different from the M. ovipneumoniae bacteria-induced cell apoptosis determined in our recent study, in which M. ovipneumoniae was demonstrated to induce the cell apoptosis through an ERK-mediated MAPK pathway [ 15 ]. The discrepancy suggested distinct pathogenic roles of CPS of M. ovipneumoniae , as compared with its parent pathogen bacteria cells.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…This observation is of particular mentioning to importance due to the fact that an inhibitor of ERK1/2 signaling is incapable of reducing the activation of caspase-3, indicating that CPS-induced apoptosis can be independent of ERK1/2 signaling and can progress alternatively through the JNK and p38 pathways. Of note, this observation was different from the M. ovipneumoniae bacteria-induced cell apoptosis determined in our recent study, in which M. ovipneumoniae was demonstrated to induce the cell apoptosis through an ERK-mediated MAPK pathway [ 15 ]. The discrepancy suggested distinct pathogenic roles of CPS of M. ovipneumoniae , as compared with its parent pathogen bacteria cells.…”
Section: Discussioncontrasting
confidence: 90%
“…In the present study, we interrogated the biological activity and mechanism of capsular polysaccharides (CPS) of M. ovipneumoniae- induced respiratory epithelial cell apoptosis using air-liquid interface- (ALI-) cultured epithelial cells generated with primary bronchial epithelial cells of Tan sheep [ 14 , 15 ]. The results showed that CPS of M. ovipneumoniae could induce sheep bronchial epithelial cell apoptosis through ROS-dependent JNK/P38 MAPK- but not ERK MAPK-mediated apoptotic pathways.…”
Section: Introductionmentioning
confidence: 99%
“…The ERK pathway has been shown to directly affect mitochondrial function by inhibiting mitochondrial respiration [ 25 ] and reducing mitochondrial membrane potential [ 26 ]. The phosphorylation of ERK1/2 leads to the disruption of mitochondrial membranes and release of cytochrome c [ 27 , 28 ]. The activation of ERK1/2 can upregulate a proapoptotic protein, such as Bax [ 29 , 30 ], and downregulate an antiapoptosis protein such as Bcl-2 [ 31 , 32 ], which facilitate the release of cytochrome c and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the main methods for detecting M. ovipneumoniae are pathogen diagnosis, enzyme linked immunosorbent assay (ELISA), and PCR (Jiang et al 2016 ) (Jiang et al 2016 ; Ziegler et al 2014 ; Li et al 2016 ; Yang et al 2014 ; Kılıc et al 2013 ). Furthermore, the research of M. ovipneumoniae has mainly concentrated on the isolation, identification, and detection technology of pathogenic bacteria (Butler et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%